2012
DOI: 10.1093/cvr/cvs357
|View full text |Cite
|
Sign up to set email alerts
|

Serum-free differentiation of functional human coronary-like vascular smooth muscle cells from embryonic stem cells

Abstract: The ability to generate hESC-derived functional human coronary-like VSMCs in serum-free conditions has implications for disease modelling, drug screening, and regenerative therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…For example, deriving coronary artery SMCs would facilitate further studies on the differences between atherosclerosis in this critical vascular bed compared to other vascular territories. Recently, El-Mounayri and colleagues [99] described a serum-free method of generating SMCs using directed differentiation of embryoid bodies towards a cardiac fate. The derived SMCs were deemed ‘coronary’ by the similarity of their Ca 2+ and contractile responses to coronary SMC controls.…”
Section: Generation Of Human Embryonic Stem Cell-derived Smooth Musclmentioning
confidence: 99%
“…For example, deriving coronary artery SMCs would facilitate further studies on the differences between atherosclerosis in this critical vascular bed compared to other vascular territories. Recently, El-Mounayri and colleagues [99] described a serum-free method of generating SMCs using directed differentiation of embryoid bodies towards a cardiac fate. The derived SMCs were deemed ‘coronary’ by the similarity of their Ca 2+ and contractile responses to coronary SMC controls.…”
Section: Generation Of Human Embryonic Stem Cell-derived Smooth Musclmentioning
confidence: 99%
“…57 Tissue-specific mesodermal VSMCs have also been generated via the EB method using a serum-free protocol to generate functional and clinically viable coronary arterylike VSMCs. 58 In fact, this study revealed that only at day 28 of EB formation did fully differentiated VSMCs appear and that these cells required the combined signaling of both VEGF and bFGF for maintenance of the phenotype ( Figure 1B).…”
Section: Embryoid Body Methodsmentioning
confidence: 80%
“…While in vitro models have only generated PC from the LPM, VSMC have been generated from the NC, LPM, PM, and CM, and display a diversity of properties that match their in vivo counterparts [19,83].…”
Section: Considering Origin Heterogeneity In Vitromentioning
confidence: 99%